Ordinary metalinguistic consciousness: an experimental analysis: Al-Farabi Kazakh National University (Eurasian Journal of Philology Science and Education, 2018)
Ordinary metalinguistic consciousness: an experimental analysisThe cultural-historical aspect of proper names, in particular, toponyms, in the last decades of the twentieth century attracted the attention of scientists. The names of geographic features are considered as an ethnocultural phenomenon, which conceals information about the boundaries of the nation’s settlement, about their historical past, cultural and trade centers and geographical, etc. The ability to nominate and describe the phenomena of reality and functional features of the place names resulted in the new and different approaches, methods of study in linguistics as well as in other branches of science. Thus, in the study of modern linguistics toponymic picture of the world refers to one of their pressing issues. The reason for this urgency has served ethnocultural and integrative status names. Under integrative status, it refers to the way the system-verbalization of reality as a reflection of the correlation of historical and social, linguistic and ethnocultural aspects of the nation’s development. Our work is to focus on the observation and interpretation of the results of Kazakhstan toponyms on the basis of the ordinary metalinguistic consciousness. The purpose of the article – to identify and describe the linguistic processes that are identified in the perception and interpretation of toponyms ordinary consciousness.